Pengaruh Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian pada Produk Konveksi Dthreee di Kota Bandung - Dinda Hijriani; Halimah Zahrah; Indra Sasangka (Indo Publishing, 2026)
Increasing competition in the convection industry encourages business actors to implement appropriate marketing strategies, in which product quality, price, and promotion are important factors influencing consumer purchasing decisions. This study aims to determine the effect of product quality, price, and promotion on purchasing decisions of DThreee convection products in Bandung City. The study employs a quantitative approach using a survey method and multiple linear regression analysis. The results show that partially, product quality, price, and promotion do not have a significant effect on purchasing decisions; however, simultaneously, these three variables have a significant effect on purchasing decisions. These findings indicate that consumer purchasing decisions are influenced by the combination of product quality, price, and promotion. Therefore, DThreee convection businesses are advised to integrate improvements in product quality with competitive pricing and effective promotional strategies.